West Nile Virus in British Columbia - Michael Aquino; Murray Fyfe; Laura MacDougall; Valencia Remple (Emerging Infectious Diseases, 2004)
We investigated personal protective behaviors against West Nile virus infection. Barriers to adopting these behaviors were identified, including the perception that DEET (N,N-diethyl-m-toluamide and related compounds) is a health and environmental hazard. Televised public health messages and knowing that family or friends practiced protective behaviors were important cues to action.